Pembangunan wakaf kesihatan: Model operasi dan pengurusan Hospital Waqaf An-Nur (HWAN) / Norizah Mohamed @ Daud … [et al.] - Mohamed @ Daud, Norizah; Mohd Aris, Noorfazreen; Abas, Sharipah Amirah; Abd Muaziz, Noraini (2017)
Waqf is a unique form of welfare in Islam because it is worship that combines both spiritual and material aspects. Waqf plays a major role in helping the government to provide services such as health and education to the society. This could be clearly seen during the golden age of Islam at the time of the Ottoman Empire. This article discusses the model of operation and management of Waqaf An-Nur Hospital (HWAN) and contribution played by the Waqf at Waqaf An-Nur Hospital (HWAN) in providing healthcare services to the local community. Health is a necessity for all, but for the poor and low-income people, health becomes a very expensive thing. The implementation of this hospital is seen as an alternative for low-income people, especially for the poor and the needy to receive medical treatment, regardless of race and religion. Data were collected by interviewing the Operations Manager and Senior Executive of WANCorp. Data from the interviews were analysed using content analysis based on themes. The results from this study show that Waqaf An-Nur Hospital is an alternative to help ease the financial burden of society in terms of health and medical care because the cost of treatment is increasing from year to year.